2020
DOI: 10.3846/jbem.2020.12217
|View full text |Cite|
|
Sign up to set email alerts
|

Macroeconomic Determinants of Corporate Failures. Evidence From Romania and Spain

Abstract: The purpose of this study is to investigate the reaction of the insolvency rate to the various shocks in the economies of Romania and Spain through a Structural Vector Autoregressive model. Departing from quarterly data for 2008–2016, it was found that the future values of the insolvency rate are explained by the past values of the interest rate and the retail trade index, more precisely macroeconomic risk factors cost of debt and changing in demand are main responsible for the health of non-financial corporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
1
0
0
Order By: Relevance
“…Conversely, a decrease in inflation could potentially enhance the profitability of SOEs during bankruptcy. This aligns with the research conclusions of Jinlan et al (2014), Huhtilainen (2020), andAnghel et al (2020), which also identified inflation as a significant factor influencing corporate bankruptcy. The other three external factors-economic growth, exchange rates, and interest rates-didnot show a significant impact on the profitability levels of SOEs in bankruptcy situations, suggesting that fluctuations in these variables did not alter the profitability outcomes of SOEs following bankruptcy.…”
Section: The Influence Of External Factors On the Firm's Bankruptcy P...supporting
confidence: 91%
“…Conversely, a decrease in inflation could potentially enhance the profitability of SOEs during bankruptcy. This aligns with the research conclusions of Jinlan et al (2014), Huhtilainen (2020), andAnghel et al (2020), which also identified inflation as a significant factor influencing corporate bankruptcy. The other three external factors-economic growth, exchange rates, and interest rates-didnot show a significant impact on the profitability levels of SOEs in bankruptcy situations, suggesting that fluctuations in these variables did not alter the profitability outcomes of SOEs following bankruptcy.…”
Section: The Influence Of External Factors On the Firm's Bankruptcy P...supporting
confidence: 91%